Analisis Model Perilaku Alumni Terhadap Supportive Outcomes pada Almamater STIE Indonesia Banking School - Santi Rimadias (Jurnal Ekonomi, Manajemen dan Perbankan (Journal of Economics, Management and Banking), 2018)
Alumni have an important role for the better of a college, like positive behaviors that can provide long-term benefits to his alma mater. This research aims to examine and analyze a model of the behavior of alumni that reflected at brand identification, prestige, satisfaction towards word of mouth, participation and financial support. This study used a survey method from 192 respondent which is the alumni of STIE Indonesia Banking School. The results of the analysis using Structural Equation Models (SEM) with the following summary: Satisfaction has a positive influence towards the brand identification, word of mouth, participation and financial support on alumni STIE Indonesia Banking School. Prestige has a positive effect on the brand identification and word of mouth, but not on the participation and financial support on alumni STIE Indonesia Banking School. Last, brand identification has a positive influence on participation, but not in word of mouth and financial support